Panel Sensory Evaluation Form for Injera - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2022)
A panel sensory evaluation form used in a field survey in Basona Werana, Ethiopia to evaluate the gendered traits preferences related to Injera